Livelihoods, poverty, and food insecurity in Myanmar: Survey evidence from June 2020 to December 2021 - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
Ten rounds of the Rural-Urban Food Security Survey (RUFSS) have been conducted between June 2020 and December 2021 to assess the impacts of Myanmar’s economic, political, and health crises on various dimensions of household welfare. RUFSS interviews about 2000 mothers of young children per round from urban Yangon, the rural Dry Zone, and recent migrants from these areas.